Plasma membrane phospholipid phosphatase-related proteins as pleiotropic regulators of neuron growth and excitability - Fuchs, Joachim; Bareesel, Shannon; Kroon, Cristina; Polyzou, Alexandra; Eickholt, Britta J.; Leondaritis, George (Frontiers in Molecular Neuroscience, 2022)
Neuronal plasma membrane proteins are essential for integrating cell extrinsic and cell intrinsic signals to orchestrate neuronal differentiation, growth and plasticity in the developing and adult nervous system. Here, we shed light on the family of plasma membrane proteins Phospholipid-phosphatase-related proteins (PLPPRs) (alternative name, PRGs; plasticity-related genes) that fine-tune neuronal growth and synaptic transmission in the central nervous system. Several studies uncovered essential functions of PLPPRs in filopodia formation, axonal guidance and branching during nervous system development and regeneration, as well as in the control of dendritic spine structure and excitability. Loss of PLPPR expression in knockout mice increases susceptibility to seizures, and results in defects in sensory information processing, development of psychiatric disorders, stress-related behaviors and abnormal social interaction. However, the exact function of PLPPRs in the context of neurological diseases is largely unclear. Although initially described as active lyso-phosphatidic acid (LPA) ecto-phosphatases that regulate the levels of this extracellular bioactive lipid, PLPPRs lack catalytic activity against LPA. Nevertheless, they emerge as atypical LPA modulators, by regulating LPA mediated signaling processes. In this review, we summarize the effects of this protein family on cellular morphology, generation and maintenance of cellular protrusions as well as highlight their known neuronal functions. We discuss the molecular mechanisms of PLPPRs including the deployment of phospholipids, actin-cytoskeleton and small GTPase signaling pathways. We distill the current state of research on PLPPR phenotypes and mechanisms, with a focus on identifying gaps in our knowledge to stimulate interest in this understudied protein family.